THE EFFECT OF GUIDING QUESTIONS TECHNIQUE ON STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT - Widya Putri Amelia; Busmin Gurning; Rita Suswati (Universitas Negeri Medan, 2015)
This study deals with the effect of Guiding Questions Technique on Students’ Achievement in Writing Descriptive Text. The objective of the study is to find out whether the students’ achievement in writing descriptive text taught by guiding questions technique is higher than that taught by using word webbing technique.. This study was conducted by using experimental design. The population of the study was the students of grade VIII of SMPN 35 Medan in the academic year 2015/2016, where there were 6 classes of VIII and there were two classes were selected as the sample by applying random sampling. The sample was divided into two groups. The Experimental group (VIII 1) was taught by applying Guiding Questions Technique, while the control group (VIII 2) was taught by applying Word Webbing Technique. The data of the study were obtained from the students’ score of writing test. To determine the reliability of the test, the writer used Pearson Product Moment formula. Based on the calculation, the coefficient of reliability of the test was 0.85. It showed that the test was reliable and the reliability was very high. There were two data used in this study. They were pre-test and post-test. After analyzing the data, the result of the study showed that t-observed (3.698) was higher than t-table (2.712) (t-observed ˃ t-table) at the level of significance of α = 0.05 and at the degree of freedom (df) = 38. The result of this study showed that students’ achievement taught by using Guiding Questions Technique is higher than that taught by using Word Webbing Technique or in other words the hypothesis is accepted. Keywords: Guiding Questions Technique, Descriptive Text